2018
DOI: 10.1016/j.envres.2018.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Household fuel use and biomarkers of inflammation and respiratory illness among rural South African Women

Abstract: Though literature suggests a positive association between use of biomass fuel for cooking and inflammation, few studies among women in rural South Africa exist. We included 415 women from the South African Study of Women and Babies (SOWB), recruited from 2010 to 2011. We obtained demographics, general medical history and usual source of cooking fuel (wood, electricity) via baseline questionnaire. A nurse obtained height, weight, blood pressure, and blood samples. We measured plasma concentrations of a suite of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…One study has reported that women who used biomass for cooking showed higher IL-6 levels than a control group [25]. A similar result was observed in another study in South Africa; those who burned wood in the home had higher plasma IL-6 levels than electricity users did [23]. These results may help explain the association between solid fuel combustion and in ammation [22].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…One study has reported that women who used biomass for cooking showed higher IL-6 levels than a control group [25]. A similar result was observed in another study in South Africa; those who burned wood in the home had higher plasma IL-6 levels than electricity users did [23]. These results may help explain the association between solid fuel combustion and in ammation [22].…”
Section: Discussionsupporting
confidence: 60%
“…Studies have revealed that in ammation is a key mechanism of human diseases caused by PM exposure. As the main in ammatory cytokines, interleukin (IL) and tumor necrosis factor-alpha (TNF-α) have been widely investigated in epidemiological and biological studies [20][21][22][23][24]. A study focusing on rural India showed that interleukin-6 (IL-6) and TNF-α levels in the serum of individuals from households that used biomass fuels were higher than in those from households that used lique ed petroleum gas (LPG) [25].…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study in Turkey reported that long-term exposure to indoor biomass smoke was associated with systolic and diastolic biventricular dysfunction, as well as increased pulmonary artery systolic pressure [ 80 ]. However, some studies have found no significant association between increased cardiovascular risk and indoor exposure to biomass smoke [ 33 , 101 , 102 , 142 ]. Indoor biomass combustion contributes to ambient air pollution, which has also been linked to increased incidence of cardiovascular outcomes.…”
Section: Cardiovascular Effects Of Wildfire Smokementioning
confidence: 99%
“…Wood, dung, agricultural residues, charcoal and coal, 1,2 are used by 3 billion people worldwide [3][4][5][6][7][8] as a primary source of cooking fuel. 9,10 Typically, these biomass fuels are relatively inexpensive and readily available, [11][12][13] with the highest usage in Low and Middle Income Countries (LMICs). 14 Rwanda is a rapidly developing country with a Gross Domestic Product (GDP) per capita of $748.3 in 2017 15 and a high prevalence of biomass fuel usage, presenting long-term health, environmental and economic issues.…”
Section: Introductionmentioning
confidence: 99%